2011
DOI: 10.1021/jm200241s
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Pharmacological Characterization of Solomonsterol A, a Potent Marine Pregnane-X-Receptor Agonist Endowed with Anti-Inflammatory Activity

Abstract: Recently, we reported the identification of a novel class of pregnane-X-receptor (PXR) agonists, solomonsterols A and B, isolated from the marine sponge Theonella swinhoei. Preliminary pharmacological studies demonstrated that these natural compounds are potential leads for the treatment of human disorders characterized by dysregulation of innate immunity. In this article, we describe the first total synthesis of solomonsterol A and its in vivo characterization in animal models of colitis. Using transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…PXR agonists have been shown to attenuate inflammatory bowel disease by reducing nuclear factor-κB target gene expression that mediates colon inflammation [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PXR agonists have been shown to attenuate inflammatory bowel disease by reducing nuclear factor-κB target gene expression that mediates colon inflammation [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Among these, solomonsterols [14], truncated chain sulfated steroids, malaitasterol A [15], an unusual bis-secosterol, and gracilioethers [16] were endowed with selective activation action on the PXR, whereas theonellasterols and conicasterols showed a dual modulatory profile on the PXR and FXR [17,18,19,20,21]. The in vivo evaluation of a synthetic sample of solomonsterol A in a colitis model using transgenic mice expressing hPXR demonstrated the effectiveness of this PXR agonist in protecting the mouse against the development of the disease [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The role of marine steroids as nuclear receptor ligands has been recently highlighted [13] and several sulfated marine steroids have been identified as a new class of the pregnane X receptor (PXR) agonists [21,22]. Based on this background, we have investigated a possible role of phallusiasterols A ( 1) and B ( 2 ) in regulating the PXR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Solomonsterol A, isolated from the marine sponge Theonella swinhoei , is a potent PXR agonist and effectively protects humanized PXR mice from developing the clinical signs and symptoms of colitis through PXR-dependent inhibition of NF-κB activation [30]. Artemisinin, a natural compound used to treat malaria, was identified as a potential PXR agonist [31], and a recent report indicated that this drug can prevent and reduce IBD development in a mouse model of DSS-induced IBD by a mechanism associated with the transcriptional activation of PXR [32].…”
Section: Pxrmentioning
confidence: 99%